2020
DOI: 10.1021/acs.jpcb.0c05842
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Allosteric Process of the Phaeodactylum tricornutum Aureochrome 1a LOV Domain

Abstract: The conformational-driven allosteric protein diatom Phaeodactylum tricornutum aureochrome 1a (PtAu1a) differs from other light-oxygen-voltage (LOV) proteins for its uncommon structural topology. The mechanism of signaling transduction in PtAu1a LOV domain (AuLOV) including flanking helices remains unclear because of this dissimilarity, which hinders the study of PtAu1a as an optogenetic tool. To clarify this mechanism, we employed a combination of tree-based machine learning models, Markov state models, machin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…In our previous studies, it was demonstrated that machine-learning-based classification for the macrostates is an effective approach to delineate protein allosteric mechanism related to individual residues. , To build effective machine-learning classification models, it is desired to have dimensionality reduction methods that could enhance the quality of classification models. We used the random forest method as a machine-learning classification model.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, it was demonstrated that machine-learning-based classification for the macrostates is an effective approach to delineate protein allosteric mechanism related to individual residues. , To build effective machine-learning classification models, it is desired to have dimensionality reduction methods that could enhance the quality of classification models. We used the random forest method as a machine-learning classification model.…”
Section: Resultsmentioning
confidence: 99%
“…16,42 To understand the mechanisms of the shear thinning behavior, the structural change of chains is examined with the . The chains' conformation is conveniently measured by calculating the mean-square end-to-end distance 19,23,[44][45][46] , which is higher than our simulated value.…”
Section: Volume Fraction Of Nanoparticlesmentioning
confidence: 64%
“…Molecular dynamics (MD) simulations represent the primary tool to investigate the conformational changes and the propagation of the allosteric signal through the allosteric network within the protein. In recent years, various studies in which MD simulations data were analyzed using advanced computational techniques, such as Machine Learning and Markov State Modeling, successfully described allosteric mechanisms of other PAS-containing proteins at atomistic level [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%